Medicinal plants of Sg. Rawog conservation area, Segaliud Lokan forest reserve, Sandakan, Sabah - Russel @ Andy Immit Mojiol; J.D. Salegin; Walter Lintangah; S.V. John; M. Patrick (Sabah Forestry Department, 2019)
The aim of the study was to determine plants that have medicinal value found in Sg. Rawog Conservation Area, Segaliud Lokan Forest Reserve in Sandakan, Sabah. The survey and data collection were conducted in selected expedition trails, namely Trail 1, 2, 3, 3A, 4 and 5. A total of 27 species of medicinal plants were recorded and categorized under six different categories. The most prominent species include Laran (Neolamarckia cadamba), Kangkawit (Uncaria lanosa), Keladi hutan (Alocasia sarawakensis), Ampalas (Tetracera scandens), Pulai (Alstonia angustiloba), Tongkat Ali (Eurycoma longifolia), Kacip Fatimah (Labisia pumila) and Wadan (Dinochloa trichogana). It was found that the categories of medicinal plants are mainly from climbers (26%), followed by woody plants (22%), herbs (19%), shrubs (15%), and ferns (11%). Other categories belong to grasses, palms & bamboos (8%).